2019
DOI: 10.1017/jfm.2019.911
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal dynamics of turbulent separation bubbles

Abstract: The spatio-temporal dynamics of separation bubbles induced to form in a fully-developed turbulent boundary layer (with Reynolds number based on momentum thickness of the boundary layer of 490) over a flat plate are studied via direct numerical simulations. Two different separation bubbles are examined: one induced by a suction-blowing velocity profile on the top boundary and the other, by a suction-only velocity profile. The latter condition allows reattachment to occur without an externally imposed favorable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 104 publications
10
70
2
Order By: Relevance
“…Again, this is fully consistent with the spectral analysis of the pressure data presented in figure 10 and confirms the presence of a low-frequency breathing mode for frequencies below 10 Hz, the intensity of which increases with the size of the TSB. This effect of TSB size is consistent with the recent DNS of Wu et al (2020), who observed a much larger variation of the reverse-flow area for a large TSB generated with a suction-only boundary condition than for a smaller TSB obtained using suction and blowing.
Figure 14.First, second and third POD modes of longitudinal velocity in the Medium TSB (arbitrary scale).
…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Again, this is fully consistent with the spectral analysis of the pressure data presented in figure 10 and confirms the presence of a low-frequency breathing mode for frequencies below 10 Hz, the intensity of which increases with the size of the TSB. This effect of TSB size is consistent with the recent DNS of Wu et al (2020), who observed a much larger variation of the reverse-flow area for a large TSB generated with a suction-only boundary condition than for a smaller TSB obtained using suction and blowing.
Figure 14.First, second and third POD modes of longitudinal velocity in the Medium TSB (arbitrary scale).
…”
Section: Resultssupporting
confidence: 91%
“…presented in figure 10 and confirms the presence of a low-frequency breathing mode for frequencies below 10 Hz, the intensity of which increases with the size of the TSB. This effect of TSB size is consistent with the recent DNS of Wu et al (2020), who observed a much larger variation of the reverse-flow area A xy (t) for a large TSB generated with a suction-only boundary condition than for a smaller TSB obtained using suction and blowing. Based on these new results, it would be of interest to plot the streamwise distribution of the fluctuating pressure coefficient for frequencies above 10 Hz only, as this would remove the pressure signature of the low-frequency breathing motion.…”
Section: Pressure Statisticssupporting
confidence: 90%
See 2 more Smart Citations
“…The separation of a turbulent boundary layer from a wall is accompanied by pressure and velocity fluctuations in a broad range of time scales. In turbulent separation bubbles (TSBs), where the separated shear layer reattaches to the wall downstream of the detachment region, at least three frequency ranges are typically observed: a low-frequency unsteadiness, usually dubbed flapping or breathing of the separation bubble, medium-frequency fluctuations, typically referring to the convection and shedding of coherent structures downstream of the separated zone, and high-frequency fluctuations related to the turbulent nature of the flow (Kiya & Sasaki 1983; Cherry, Hillier & Latour 1984; Hudy, Naguib & Humphreys 2003; Mohammed-Taifour & Weiss 2016; Wu, Meneveau & Mittal 2020).…”
Section: Introductionmentioning
confidence: 99%